Robusta coffee processing productivity analysis using objective matrix (OMAX) method (Case study at PT Tinkerbels Permata Indah, Bogor, West Java) - Deoranto, Panji; Hilal, Abiyyu Yazid; Purwaningsih, Isti (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
PT Tinkerbels Permata Indah is one of the companies engaged in the coffee processing industry. The high market demand for coffee products made from robusta coffee requires PT Tinkerbels Permata Indah to continuously produce more coffee effectively and efficiently. Therefore, companies need to measure productivity to determine the performance of using several inputs to produce output. This research aimed to analyze the productivity level of robusta coffee bean production and to make a proposed improvement plan for PT Tinkerbels Permata Indah. The method used to measure productivity was the objective matrix (OMAX) method. The weight of each criterion was obtained with the help of the pairwise comparison method by filling out a questionnaire by the three experts involved. The results show that the company's highest productivity achievement was 5.893 in April 2022, and the lowest was in September 2022, with a current value of 0.880. Proposed improvements include companies needing to pay attention to their warehouses by maintaining temperature and humidity so that materials are not damaged by warehouse pests, implementing flexible daily hours to reduce wastage of employee work time, implementing an energy-saving culture, conducting energy audits, and implementing machinery maintenance management.